2022
DOI: 10.3389/fmicb.2022.928921
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Shaping the Diversity and Spatial-Temporal Distribution of Indoor and Outdoor Culturable Airborne Fungal Communities in Tianjin University Campus, Tianjin, China

Abstract: Airborne fungi have significant influence on air quality and may pose adverse effects on human health due to their allergenic and pathogenic effect. We carried out a 1-year survey on the airborne fungal diversity and concentration of indoor and outdoor environments, within the Tianjin University campus. Airborne fungi were sampled using an HAS-100B air sampler. Isolated fungal strains were identified based on morphological and molecular analysis. A total of 641 fungal strains belonging to 173 species and 74 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Spores of Cladosporium species are known to be widely dispersed in the air globally, and are the major airborne spores in temperate areas 35 . Our study results are consistent with other results 23 , 49 , 61 63 . Out of 772 taxa of Cladosporium, only 170 has recently been recognized as distinct species with C. cladosporioides, C. herbarum, and C. sphaerospermum being considered the three major species complexes 64 .…”
Section: Resultssupporting
confidence: 94%
“…Spores of Cladosporium species are known to be widely dispersed in the air globally, and are the major airborne spores in temperate areas 35 . Our study results are consistent with other results 23 , 49 , 61 63 . Out of 772 taxa of Cladosporium, only 170 has recently been recognized as distinct species with C. cladosporioides, C. herbarum, and C. sphaerospermum being considered the three major species complexes 64 .…”
Section: Resultssupporting
confidence: 94%
“…In a study conducted on infants with asthma, Gent et al (2002) reported that the higher Penicillium concentrations were linked to a higher likelihood of wheezing and chronic cough. Seasonal changes in the environment are known to determine important variations in outdoor airborne fungal communities (Larsen, 1981;Kumar et al, 2021;Núñez et al, 2021;Yuan et al, 2022). We found a significant difference in fungal concentration in the analyzed environments in Tianjin, with the highest level recorded in spring and the lowest in winter.…”
Section: Discussionmentioning
confidence: 72%
“…Seasonal changes in the environment are known to determine important variations in outdoor airborne fungal communities ( Larsen, 1981 ; Kumar et al, 2021 ; Núñez et al, 2021 ; Yuan et al, 2022 ). We found a significant difference in fungal concentration in the analyzed environments in Tianjin, with the highest level recorded in spring and the lowest in winter.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling of airborne fungi was carried out in Tianjin University campus, Tianjin city, China. This study was conducted as part of a larger work, which analyzed the whole airborne fungal community in the selected university environments [ 25 ]. Six different sites, including one outdoor and five indoor environments, were selected to collect the air samples (see Yuan et al, 2022 [ 25 ] for details).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as part of a larger work, which analyzed the whole airborne fungal community in the selected university environments [ 25 ]. Six different sites, including one outdoor and five indoor environments, were selected to collect the air samples (see Yuan et al, 2022 [ 25 ] for details). The sampling was conducted every month, from June 2020 to May 2021.…”
Section: Methodsmentioning
confidence: 99%